Fraud Control to Strengthen Internal Control Systems in Local Goverment - Wuryandini, Ayu Rakhma; Pakaya, Lukman; Husain, Siti Pratiwi (International Journal of Applied Business and International Management, 2023)
Talking about fraud in Indonesia is endless, negligence can lead to fraud, but this fraud can be controlled early with proper internal controls. Fraud will always exist where there are opportunities and weaknesses. Every effort should be made by the organization to prevent and control fraudulent acts. The government agencies in Bone Bolango is a government organization that implements the Fraud Control Plan control tool. The purpose of this research is to analyze the existence and application of the Fraud Control Plan attributes in the work environment of the organization. The research method in this research is descriptive qualitative with a case study at government agencies in Bone Bolango Regency, Gorontalo Province. The results of this study that this government agencies has a good assessment in realizing the performance of Good Governance in the criteria of "Sufficiently adequate" in an indication of a reduction in fraud and an increase in employee performance in the organization. the important value of the presence of fraud control for agencies is the accountability of each attribute value reflects the transparency of each activity. Control of each agency is more controlled and positively directed and further minimizes the occurrence of fraud. The value that can be drawn from this research is the achievements that have been made optimally so that they can be properly maintained, and for elements that have not been fulfilled so that they can be corrected immediately in accordance with local government procedures and policies. The next researcher should consider the other methods used.